Women's rights and global socialism - Donert, Celia, 1975- 1975- Herausgeber; Moll-Murata, Christine 1960- Herausgeber (International review of social history / Special issue;, 2022)
This Special Issue explores the complicated relationship between women's rights and global socialism during the Cold War. This Introduction describes how the articles deal with this relationship in three, partly overlapping, periods. The first set of articles looks at how the ethos of the Popular Front resonated among women's movements in Asia, Latin America, and Europe, and examines the connections between interwar anti-fascist and anti-imperialist feminisms and those that re-emerged after World War II. The second set of articles focuses on the role and development of the Women's International Democratic Federation (WIDF) and its model of internationalism in Eastern Europe, the Soviet Union, and China in the early Cold War. The final articles centre on the challenges faced by the WIDF from the 1960s, exploring issues such as the anti-apartheid struggles in South Africa, the Portuguese wars of decolonization, and the United Nations Decade for Women (1976–1985). Together with this process of decolonization, this Special Issue also examines how the consequences of postsocialism, in particular for women's rights (the loss of social rights, material security, and substantial challenges to reproductive freedoms), have triggered renewed debates about the history and legacies of communist women's liberation movements in the former socialist world.